Analysis of beef cattle marketing channels under transaction costs in rural Ethiopia - Dinku, A; Abede, B; Lemma, A; Shako, M (International Journal of Agricultural Research, Innovation and Technology, 2021)
The study was designed to analyze beef cattle marketing channel choice under transaction costs. Multistage sampling technique was used to acquire primary data. Data were analyzed using descriptive statistics and the Multinomial Logit Model. The findings verified that most of the respondents (49%) were selling at the village markets, followed by farm gate and secondary market with 28% and 23%, respectively. The model results revealed that the probability of selling at farm gate and village market versus selling at secondary market increased with season sales, indicating level of market uncertainty. The results affirmed the probability of selling at village market versus selling at secondary market outlet increased with knowledge of buyer and decreased with trust in buyers. Other significant predictors were volume of beef cattle supplied, farmers' experience, and education level. Thus, policies aimed at improving the smallholder farmers’ access to cattle marketing channels should be informed by these factors. Int. J. Agril. Res. Innov. Tech. 11(1): 37-48, June 2021